Too Many Meanings: Contestation of Lawang Sewu as a Heritage Tourism Attraction - Uswatun Nurul (Gadjah Mada Journal of Tourism Studies, 2018)
Tourism industry utilizes heritage as a tourist attraction. Not only the physical existences, but also the meaning of its heritage, particularly its narrations, are used to gain profit for tourism industry. Lawang Sewu located in Semarang, Indonesia is one heritage which is used by PT KeretaApi Indonesia (PT KAI) as a heritage tourism attraction. This research analyses many meanings or narrations of Lawang Sewu as a heritage tourism attraction. This research has three objectives. First, it aims to identify the meaning of BPCB Central Java, PT KAI, local people, tour guides and tourist interpretations of Lawang Sewu. Second, it aims to discover which stakeholder dominates the narrations presented in Lawang Sewu. Third, it seeks to understand how the dominant stakeholder can govern the narrations. This research is a qualitative research with inductive reasoning. Through the use of interactive analysis model as the data analysis method and hermeneutics approach to draw the conclusion, this research finds that each stakeholder construes the meaning of Lawang Sewu differently. Among the interpretations, PT KAI is the dominant stakeholder found in the presentation of Lawang Sewu to tourists.